[en] FIELDING THE STATE: STATE PARTICIPATION IN INTERNATIONAL LAND ACQUISITIONS IN ETHIOPIA FROM 2003 TO 2012 - FRANCO NAPOLEAO AGUIAR DE ALENCASTRO GUIMARAES (MAXWELL, 2019)
[pt] O aumento no número de aquisições internacionais de terras nas últimas duas décadas motiva pesquisas sobre os atores envolvidos neste processo e responsáveis por esta intensificação. Nesta dissertação, é analisado o papel do Estado na criação das condições de possibilidade para as aquisições internacionais de terras, a partir de um estudo de caso, o Etíope. São examinados os mecanismos e regulações criados pelo Estado, o contexto histórico e internacional para sua atuação, e as finalidades econômicas e políticas para as mesmas, a partir de um referencial teórico baseado no conceito de acumulação por espoliação elaborado por David Harvey. === [en] The increase in the number of international land acquisitions in the last two decades calls for research on the actors involved in this process and responsible for this intensification. In this dissertation, the role of the State in creating the conditions for these acquisitions is examined through a case study, Ethiopia. Mechanisms and regulations created by the State are analyzed, along with the local historical and international context for the State s policies and its political and economic aims, with the deployment of a theoretical framework based on the concept of accumulation by dispossession as developed by David Harvey.